Innovative applications of biochar in nuclear remediation and catalysis - Mojtaba Kordrostami; Ali Akbar Ghasemi-Soloklui (Biochar)
Abstract Emphasizing its potential for environmental sustainability, this review investigated how biochar—a carbon-rich material obtained from biomass pyrolysis—might be used into nuclear science and technology. High surface area, porosity, and functional groups give biochar special adsorption capacity, which qualifies it as a potential instrument for radiation cleanup and improving energy economy in nuclear uses. From the historical development of nuclear physics to the creative application of biochar in nuclear waste management and radiation shielding as well as its contribution to sustainable nuclear energy, the study covers several spheres. Biochar presents amazing efficiency in adsorbing and immobilizing radionuclides in the field of nuclear waste management, therefore establishing itself as a viable substitute for more traditional approaches. Its uses cover handling of high-level radioactive materials as well as treating low-level radioactive effluents. The paper also looks at using biochar as radiation shielding since its carbonaceous character produces strong, light-weight protective barriers. Using controlled pyrolysis and later changes, the paper addresses advanced manufacturing processes for customizing nuclear-grade biochar for particular uses. Within the nuclear industry, economic studies emphasize the affordability and possible financial gains of biochar, as well as its market potential and commercialization techniques. Lifetime analysis helps to evaluate environmental effects and sustainability by stressing the part of biochar in carbon sequestration and lowering of ecological footprints. The paper discusses safety and regulatory issues, how artificial intelligence and machine learning might be used for material optimization, and the limits and difficulties in using biochar. Practical case studies highlight its success in nuclear environments. The study ends by placing biochar as a major component in creating sustainable nuclear technology, which calls for continuous research, cooperation, and creativity. Graphical Abstract